Sexual disinhibition and dementia. Issue 2 (28th July 2015) - Cipriani, Gabriele; Ulivi, Martina; Danti, Sabrina; Lucetti, Claudio; Nuti, Angelo
Abstract: To describe inappropriate sexual behaviour (ISB) observed in patients with dementia, we conducted searches using the Cochrane Library, PubMed, and Web of Science to find relevant articles, chapters, and books published from 1950 to 2014. Search terms used included 'hypersexuality', 'inappropriate sexual behaviors', and 'dementia'. Publications found through this indexed search were reviewed for further relevant references. Sexuality is a human's need to express intimacy, but persons with dementia may not know how to appropriately meet their needs for closeness and intimacy due to their decline in cognition. Generally, the interaction among brain, physical, psychological, and environmental factors can create what we call ISB. The most likely change in the sexual behaviour of a person with dementia is indifference. However, ISB in dementia appear to be of two types—intimacy‐seeking and disinhibited—that differ in their association with dementia type, dementia severity and, possibly, other concurrent behavioural disorder. Tensions develop from uncertainties regarding which, or when, behaviours are to be considered 'inappropriate' (i.e. improper) or abnormal. While most ISB occur in the moderate to severe stages of Alzheimer's dementia, they may also be seen in early stages of frontotemporal dementia because of the lack of insight and disinhibition. ISB are often better managed by non‐pharmacological means, as patients may be less responsive to psychoactive therapies, but non‐pharmacological interventions do not always stop the behaviour.